Implementasi Sistem Informasi Monitoring Survei SUSENAS dengan Metode RAD pada BPS Kabupaten Luwu Timur - Deni Candra Saputra; Migunani Migunani; Maya Utami Dewi; Khoirur Rozikin; Arsito Ari Kuncoro (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study aims to develop a web-based information system to facilitate the monitoring process of the National Socio-Economic Survey (SUSENAS) activities conducted by partners of the Central Bureau of Statistics (BPS) in Luwu Timur Regency. The main issues identified include the use of manual methods, such as Google Sheets for partner monitoring, and the Pencil and Paper Interviewing (PAPI) method for marking survey area coordinates, both considered inefficient and prone to errors. The system development employed the Rapid Application Development (RAD) method, which allows for an iterative process and active user involvement in every development phase. The result of this study is an information system equipped with project management features, real-time partner monitoring, survey reporting through document uploads, and survey location tracking integrated with OpenStreetMap using the Leaflet.js library. The developed system has proven effective in enhancing the accuracy, efficiency, and overall effectiveness of SUSENAS field operations.